2020
DOI: 10.1111/ajag.12894
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low‐intake dehydration among older inpatients: A pilot study

Abstract: Objectives: To assess fluid intake among older inpatients and factors associated with low-intake dehydration. Methods: Daily fluid intake and access were assessed within the 24-hour period, and blood was drawn to measure serum osmolality. Results: Of 89 patients, 16% and 27% had serum osmolality ≥ 300 (dehydrated) and 295-299 mOsm/kg (impending dehydration), respectively. Median (IQR) total fluid intake was 1.7 (1.6, 1.9) L/day. Fluid intake from beverages (P = .06) and water (P = .02) was higher in hydrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Another recent study [6] identified that older patients with bladder continence issues had the lowest water intake of <300 ml per day and that this was associated with 7.8 times greater odds of dehydration (odds ratio 7.8, 95% CI 1.8–34). Simple strategies such as offering water at routine intervals such as each meal, snack and with medications was described as a simple strategy likely to be of benefit.…”
Section: Practical Strategies To Prevent and Manage Geriatric Dehydra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent study [6] identified that older patients with bladder continence issues had the lowest water intake of <300 ml per day and that this was associated with 7.8 times greater odds of dehydration (odds ratio 7.8, 95% CI 1.8–34). Simple strategies such as offering water at routine intervals such as each meal, snack and with medications was described as a simple strategy likely to be of benefit.…”
Section: Practical Strategies To Prevent and Manage Geriatric Dehydra...mentioning
confidence: 99%
“…Poor vision or mobility may limit access to fluid, especially if hospitalized or in long-term care. For elders who are reliant on feeding assistance, this is a known risk factor for low fluid intake [6], and elders may be inclined to not ask for assistance with hydration or be a burden to others.…”
Section: Causes Of Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation